Protecting farmers or protecting institutions? An analysis of strategies to leverage high-quality development of county-specific agricultural insurance - Zhuo Zhang; Ming Wang (Humanities & Social Sciences Communications)
Abstract The lagging development of agricultural insurance in the field of new agricultural and specialty agricultural products has become an inherent cause of structural imbalance in China’s agricultural insurance market. How to leverage the new agricultural products agricultural insurance market with limited financial payment capacity is especially critical to promote high-quality agricultural development. This paper constructs an evolutionary game analysis model of government-farmers-insurance companies and compares the effects of two differential subsidy models, “subsidizing farmers” and “subsidizing institutions”, on the participation and underwriting strategies of new agricultural insurance products. The conclusions show that only when the insurance company has positive returns (E-F > 0) can the insurance company provide insurance services, and the government provides subsidies for operating costs to ensure that the insurance company does not operate at a loss, which is the single strategic support condition for the insurance company to provide insurance products. The “insured farmers” approach, due to the scale effect of the insured farmers, will make the insurance company to ensure the profitability, raise the premium level or compress the market size. The adjustment of financial subsidies from “insuring farmers” to “insuring institutions” can ensure that the business scale of insurance companies can effectively leverage the supply of special agricultural insurance. Finally, this paper puts forward suggestions for the optimization of agricultural insurance policies in new agricultural business fields.